Mobile app glossary of terms in Islamic Banking and finance (Arabic-Malay-English) via IOS & Android based devices. - Dollah, Nafi@Hanafi; Mohd Ghalib, Mohd Feham; Sahrir, Muhammad Sabri; Zakaria, Abdul Wahab; Omar, Zakaria; Hassan, Rusni (2017)
The expansion of Islamic banking practices through various local financial institutions which received vast attention nowadays by educationists and learners for instance, leads to the need in understanding the terminologies used in the industry. In view of this scenario, the project shed some light on using a workable model for developing a purposeful mobile Islamic banking terminology glossary application in a more convenient way via mobile devices such as iPhone, iPad or any Android-based smart gadgets. The mobile terminology glossary app was designed by using a developmental research design using via rapid prototype instructional design model. Since the use of mobile technology is very much pervasive, more work should be done to know how best we might use it to support teaching and learning processes.